Diagnóstico agroambiental do município de Natuba, Paraíba - Cunha, Josevaldo Pessoa da (2014)
This study aimed to carry out a diagnosis of the agro-environment in the municipality of Natuba, Paraíba, and propose some intervening actions consonants with the sustainable use of the natural resources and production systems. Situated in the Serra do Pirauá, one segment of the eastern front of the Borborema Plateau, the municipality of Natuba integrates the series of Brejos, a more humid altitudinal environment, that are distributed along the border Paraíba / Pernambuco. Under specific soil and climatic conditions, it developed, in the eastern portion of the county, a native humid forest, now quite altered by man, which was replaced by agriculture, especially bananas and grapes, and, on a smaller scale, subsistence crops. The remaining portion is dominated by caatinga. The choice of the municipality of Natuba for this work is justified by two factors: the area is subject to conditions of social and ecological stress; the ecosystem of the Brejos is still little known. Bibliographic and cartographic survey was the first step and served as the theoretical basis for the development of the field work and analysis of secondary data. Furthermore, interviews with experts and farmers in the city were held, as well as several field observations, in order to know the local reality, identify their potential, get information on availability and current state of the conservation of natural resources, identify and characterize forest remnants, the type of extraction practiced and production systems and dominant land tenure structure . The information obtained directly and selected secondary data were summarized in tables. From the general diagnosis of the city, two distinct agro-environmental zones, the Brejo and the Agreste were identified. These areas have their social indicators, production system and natural framework quite different. The Brejo occupies about 40% of the territory and the remaining 60% is occupied by the Agreste. Plans and programs for sustainable development of Natuba should take these differences in account